Single-walled carbon nanotubes as delivery vehicles enhance the immunoprotective effects of a recombinant vaccine against Aeromonas hydrophila. Issue 1 (January 2015) - Gong, Yu-Xin; Zhu, Bin; Liu, Guang-Lu; Liu, Lei; Ling, Fei; Wang, Gao-Xue; Xu, Xin-Gang
Abstract To reduce the economic losses caused by diseases in aquaculture industry, more efficient and economic prophylactic measures should be urgently investigated. In this research, the effects of a novel functionalized single-walled carbon nanotubes (SWCNTs) applied as a delivery vehicle for recombinant Aeromonas hydrophila vaccine administration via bath or injection in juvenile grass carp were studied. The results showed that SWCNT as a vector for the recombinant protein aerA, augmented the production of specific antibodies, apparently stimulated the induction of immune-related genes, and induced higher level of survival rate compared with free aerA subunit vaccine. Furthermore, we compared the routes of bath and intramuscular injection immunization by SWCNTs-aerA vaccine, and found that similar antibody levels induced by SWCNTs-aerA were observed in both immunization routes. Meanwhile, a similar relative percentage survival (approximately 80%) was found in both a 40 mg/L bath immunization group, and a 20 μg injection group. The results indicate that functionalized SWCNTs could be a promising delivery vehicle to potentiate the immune response of recombinant vaccines, and might be used to vaccinate juvenile fish by bath administration method.